The Implementation of Literacy-Based Learning to Improve the Quality of Madrasah Education in Agam Regency - Ali Mutasar; Rifma Rifma; Syahril Syahril (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2026)
This study aims to analyze the implementation of literacy-based learning in improving the quality of madrasah education in Agam Regency. The study employed a qualitative approach with a document analysis design. The primary data were derived from the 2025 National Computer-Based Assessment (Asesmen Nasional Berbasis Komputer—ANBK), covering 8 State Islamic Elementary Schools (MIN), 13 State Islamic Junior Secondary Schools (MTsN), and 5 State Islamic Senior Secondary Schools (MAN), supported by relevant literature and educational policy documents. The data were analyzed through data reduction, presentation, interpretation, and conclusion drawing. The findings revealed that 76.9% of the madrasahs achieved a good literacy category, while 23.1% remained in the moderate category. Despite generally positive literacy achievement, the quality of learning in several madrasahs remained moderate. The implementation of literacy-based learning encountered challenges, including teacher-centered instruction, memorization-oriented learning, limited reading interest, and the underutilization of literacy facilities and ANBK results. Strengthening contextual, problem-based, project-based, reflective, and digital literacy learning is necessary to improve educational quality. The integration of Islamic values, including iqra’, tabayyun, ṣidq, amānah, and ta‘āwun, further supports the development of students’ intellectual competence, spiritual awareness, and character.